COMPLEX TREATMENT OF ACUTE NONSPECIFIC PLEURAL EMPYEMA - I. V. Nikolaychuk; A. N. Plekhanov (Acta Biomedica Scientifica)
In the article the results of complex treatment of acute pleural empyema in 123 patients are presented. In all cases we observed pleural empyema of nontraumatic character. Positive results of treatment of patients with this pathology are marked in patients whose complex of treatment included laser therapy.